Midwifery Care Management for Threatened Abortion in Early Pregnancy: A Qualitative Descriptive Study and Document Review at Medan Haji Hospital - Agnes Mutiara Simorangkir; Raina Fadhilah; Asi Esterina Sarumpaet; Indira Virli Ananda; Dara Lestari; Juliana Munthe; Nelly Zahara (Asosiasi Dosen Muda Indonesia, 2026)
Threatened abortion (abortus imminens) is a common early-pregnancy condition characterized by first-trimester vaginal bleeding with a closed cervix and an ongoing intrauterine pregnancy. Besides clinical risk, it frequently produces psychological distress and is influenced by socioeconomic barriers, health literacy, and the coordination of care across providers and families. Objective: This study aimed to describe and analyze midwifery care management for women with threatened abortion at approximately 8 weeks’ gestation at Medan Haji Hospital, using an SDG-oriented lens on access (SDG 1), education/health literacy (SDG 4), and partnerships (SDG 17). Methods: A qualitative descriptive approach was combined with a desk-based document review. Primary information was collected through semi-structured interviews with women receiving care for threatened abortion in the Jabal Uhud UPTD Room. Secondary information was obtained from peer-reviewed literature, midwifery textbooks, and official reports/guidelines. Data were analyzed through thematic categorization and integrated by triangulation to synthesize patterns across access, education, and partnership domains. Findings: Three major patterns emerged. First, economic and transportation/coverage constraints were consistently linked to delayed or fragmented antenatal care and follow-up, weakening early detection and safety-netting. Second, limited health literacy and inconsistent counseling contributed to delayed care-seeking and suboptimal adherence to follow-up recommendations. Third, stronger partnerships interprofessional coordination, facility-to-system linkages, and family (including husband) support were associated with clearer referral pathways, improved continuity of care, and better emotional support for women experiencing early pregnancy bleeding. Implications: A continuity-oriented midwifery care bundle is recommended, integrating standardized counseling and return precautions, structured follow-up planning, and partnership mechanisms involving interprofessional coordination and family engagement to improve early pregnancy care quality and maternal well-being. Originality/Value: This study offers an integrated, SDG-linked interpretation of threatened-abortion midwifery care management by connecting clinical processes with structural access barriers, maternal health literacy, and partnership mechanisms, providing a practical framework for service improvement.